Histone deactylase 1 expression is increased in the prefrontal cortex of schizophrenia subjects: Analysis of the National Brain Databank microarray collection - Sharma, Rajiv P.; Grayson, Dennis R.; Gavin, David P. (Schizophrenia research, 2008)
Histone deactylase enzymes are responsible for the deacetylation of histone tails, and consequently influence gene regulation through their ability to modify chromatin structure surrounding promoter regions. We analyzed the microarray collection of the National Brain Databank to investigate differential expression of these enzymes in the prefrontal cortices of control, schizophrenia and bipolar subjects. HDAC1 expression levels were significantly higher in schizophrenia versus normal subjects. The mRNA expression level of an epigenetically regulated schizophrenia candidate gene GAD67 was strongly and negatively correlated with the mRNA expression levels of HDAC1, HDAC3 and HDAC4 levels. These findings provide additional support for the proposal that epigenetic factors are operative in the brain pathology of patients with schizophrenia.